Leukocytosis and Expression of Bovine Leukemia Virus microRNAs in Cattle - Kosovsky, Gleb Yu.; Glazko, Valery I.; Glazko, Galina V.; Zybaylov, Boris L.; Glazko, Tatiana T. (Frontiers in Veterinary Science, 2020)
Bovine Leukemia Virus (BLV) is an established model for studying retroviral infections, in particular the infection by the human T-cell leukemia type 1 (HTLV-1) virus. Here, we quantified gene expression of several BLV-related genes: effector protein of T and NK-killer cells NK-lysin (Nklys), reverse BLV transcriptase pol, BLV receptor (blvr), and also key enzymes of the microRNA maturation, Dicer (dc1) and Argonaut (ago2). The differences in the expression of the above genes were compared between five groups: 1) BLV infected cows with high and 2) low lymphocyte count, 3) with and 4) without BLV microRNA expressions, and 5) cows without BLV infections (control group). As compared to control infected cows with high lymphocyte count and BLV microRNA expression had significantly decreased Nklys gene expression and increased dc1 and ago2 gene expressions. Few infected animals without pol gene expression nevertheless transcribed BLV microRNA, while others with pol gene expression didn’t transcribe BLV microRNA. Notably, Pol expression significantly (P<0.05) correlated with dc1 expression. For infected animals there were no direct correlations between the number of leukocytes and pol, Nklys and BLV microRNA gene expressions. Blvr gene expression is typical for juvenile lymphocytes and decreases during terminal differentiation. Our data suggest that BLV infects primarily juvenile lymphocytes, which further divide into two groups. One group expresses BLV DNA and another one expressed BLV microRNA that decreases host immune response against cells, expressing BLV proteins. It is suspected that regulatory microRNAs play a significant role in the bovine leukemia infections, yet the precise mechanisms and targets of the microRNAs remain poorly defined. Vaccines that are currently in use have a low response rate. Understanding of microRNA regulatory mechanisms and targets would allow to develop more effective vaccines for retroviral infections.